Size effect in the flexural strength of ice - Williams, F. M.; Parsons, B. L. (1994)
This paper presents the first results of an empirical study of the simultaneous dependence of flexural strength of ice on five physical parameters: brine volume, sample size, grain diameter, temperature and strain rate. Recent field and laboratory projects at IMD have provided a substantial data base in which all of these parameters were documented. To extend the range of the parameters, the in-house data were combined with data obtained from the open literature. Statistical analysis showed that after brine volume, sample size has the strongest effect on flexural strength. This effect was quantified, and the results were applied to the interpretation of ice data for the design of offshore structures and ships. NRC publication: Yes